Effort Estimation For Software Development On Mobile Application Of 'Tangkap Reptil' - Condro Kartiko; Novanda Alim Setya Nugraha; Dery Sudrajat (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2019)
An essential aspect of planning and management of software design projects is to estimate work time, costs, and human resources. The calculation solution made in this study aims to assist in calculating the estimated time of developing a reptile capture application using the Use Case Point (UCP) method. The UCP method is a software effort estimation method that shows better performance compared to other methods. The result of this research is the risk of software development on the mobile application of 'Tangkap Reptil' has a small chance, can be done in a relatively short time, and does not require a lot of resources.